1997
DOI: 10.1051/aas:1997183
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of seven face-on spiral galaxies

Abstract: Abstract. We continue in this work the study of nearby spiral galaxies started with NGC 628 (Natali 1992, hereafter Paper I). A sample of seven face-on spiral galaxies has been selected to obtain images in the U , B, V , R, I bands using a CCD detector at the 90 cm Schmidt telescope at Campo Imperatore Observatory. Surface photometry using a dedicated software is used to derive both the surface brightness radial profiles in each band and the colour indexes. The radial disk scalelengths obtained from the radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Secondly, for systems with small bulges MacArthur et al (2003) showed that results from one-dimensional photometry are equivalent to those derived from two-dimensional fits (as required by this work). The resulting sample is comprised of 61 galaxies taken from Möllenhoff (2004), MacArthur et al (2003), Prieto et al (2001) and Pompei & Natali (1997). Since MacArthur et al had measurements in B V R H, their R band scalelengths were converted to I band scalelengths by multiplying them by a factor of 0.981.…”
Section: Application To Local Universe Disk Galaxiesmentioning
confidence: 99%
“…Secondly, for systems with small bulges MacArthur et al (2003) showed that results from one-dimensional photometry are equivalent to those derived from two-dimensional fits (as required by this work). The resulting sample is comprised of 61 galaxies taken from Möllenhoff (2004), MacArthur et al (2003), Prieto et al (2001) and Pompei & Natali (1997). Since MacArthur et al had measurements in B V R H, their R band scalelengths were converted to I band scalelengths by multiplying them by a factor of 0.981.…”
Section: Application To Local Universe Disk Galaxiesmentioning
confidence: 99%
“…However, we oftenly face again the problem of disjunct samples (e.g. Kent 1985;Prieto et al 1992;Courteau 1996;Pompei & Natali 1997;Lu 1998). Héraudau & Simien (1996) presented CCD photometry in V and I of 234 spiral galaxies.…”
Section: Comparison With Previous Papersmentioning
confidence: 99%
“…This effect was later also observed in many galaxies by a number of observational groups, both in edge-on galaxies (Jensen & Thuan 1982;Sasaki 1987;Fry et al 1999;Barteldrees & Dettmar 1994;Pohlen et al 2000a;de Grijs et al 2001;Kregel et al 2002), and also in face-on galaxies (Pompei & Natali 1997;Pohlen et al 2002). For a recent summary of this topic, see van der Kruit (2001).…”
Section: Introductionmentioning
confidence: 65%